An application of network theory to territorial analysis: The case of Yaqui Valley networks (2006 and 2016) - Hernández Hernández , Ma. Leticia; Gallardo Cobos, Rosa; Dios-Palomares, Rafaela; Martínez Pellégrini, Sárah Eva (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
The Yaqui Valley territory in the northwest of Mexico was analyzed using networks theory that determines the flows density and actors centrality among the agricultural sector. These networks were those of public, financial, commercial, technical, and social policy management. The current research has been carried out with the general objective of identifying the actors that make up the networks in the Yaqui territory and their change in densities as one of the factors that determine the effectiveness of the policy applied in the territory, comparing two samples of 2006 and 2016. Linked to this objective, it is proposed to describe the obstacles for the densification of networks that favor the agricultural producers labor in the Yaqui Valley territory. The obtained results indicate a clear disarticulation in the different networks of study that can elicit serious social problems of inequality among the actors that are active in the agricultural sector. The networks found in the territory of the Yaqui Valley have been disarticulated over time, because ten years after being analyzed for the first time, the calculation of densities has been reduced by 24% on average, and the truss of the social sector practically tends to disappear.